Freddy the frogcaster and the big blizzard - Dean, Janice, 1970- (Freddy the frogcaster, 2014)
Freddy the frogcaster needs to warn the frogs about the blizzard blowing toward Lilypad. Includes an introduction to the science behind winter weather and downloadable checklists and activity ideas.